High Pseudocapacitance‐Driven CoC2O4 Electrodes Exhibiting Superior Electrochemical Kinetics and Reversible Capacities for Lithium‐Ion and Lithium–Sulfur Batteries. Issue 52 (7th November 2022) - Zhou, Zhiming; Lin, Peirong; Zhao, Shiqiang; Jin, Huile; Qian, Yudan; Chen, Xi, an; Tang, Xinyue; Zhang, Qingcheng; Guo, Daying; Wang, Shun
Abstract: In this study, cuboid‐like anhydrous CoC2 O4 particles (CoC2 O4 ‐HK) are synthesized through a potassium citrate‐assisted hydrothermal method, which possess well‐crystallized structure for fast Li + transportation and efficient Li + intercalation pseudocapacitive behaviors. When being used in lithium‐ion batteries, the as‐prepared CoC2 O4 ‐HK delivers a high reversible capacity (≈1360 mAh g ‐1 at 0.1 A g ‐1 ), good rate capability (≈650 mAh g ‐1 at 5 A g ‐1 ) and outstanding cycling stability (835 mAh g ‐1 after 1000 cycles at 1 A g ‐1 ). Characterizations illustrate that the Li + ‐intercalation pseudocapacitance dominates the charge storage of CoC2 O4 ‐HK electrode, together with the reversible reaction of CoC2 O4 +2Li + +2e − →Co+Li2 C2 O4 on discharging and charging. In addition, CoC2 O4 ‐HK particles are also used together with carbon–sulfur composite materials as the electrocatalysts for lithium–sulfur (Li–S) battery, which displays a gratifying sulfur electrochemistry with a high reversibility of 1021.5 mAh g −1 at 2 C and a low decay rate of 0.079% per cycle after 500 cycles. The density functional theory (DFT) calculations show that CoC2 O4 /C can regulate the adsorption‐activation of reaction intermediates and therefore boost the catalytic conversion of polysulfides. Therefore, this work presents a new prospect of applying CoC2 O4 as the high‐performance electrode materials for rechargeable Li‐ion and Li–S batteries. Abstract : Well‐crystallized CoC2 O4 particles are synthesized by the chelating agent‐assisted hydrothermal method, which display fast Li + transportations and efficient Li + intercalation pseudocapacitive behaviors to achieve outstanding Li‐ion performance. CoC2 O4 particles are also used together with carbon–sulfur composite materials as the electrocatalysts for lithium–sulfur battery, which delivers a gratifying sulfur electrochemistry with a high reversibility and long cycling lifespan.